Multi-objective Optimal Design of Double Helical Gear Transmission based on Parameter Sensitivity Analysis - Guan Yabin; Yang Xiaohui; Fang Zongde (Jixie chuandong)
Based on the fact that the carrying capacity cannot be made the best use of because of the large difference between safety factor of surface durability and bending strength,and the large calculation caused by the many design parameters during the aero- engine double helical gear transmission design,the minimum weight and difference between each gear’s safety factor of surface durability and bending strength are taken as the objective functions. The design parameters which are important to the objects are chosen as optimization variables based on parameter sensitivity analysis method. Finally,the optimization solution is carried out by using the NSGA- Ⅱ. The results of optimization design show that the method promoted can effectively reduce the difference of the safety factors and the weight of the transmission system.